2019
DOI: 10.1002/adem.201801331
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Design and Fabrication of Strong and Ductile (Tensile) Titanium Metal Matrix Composites

Abstract: Titanium metal matrix composites (TiMMCs) offer much improved strength, elastic modulus, and wear resistance at both room and elevated temperatures but often at the expense of tensile ductility, which excludes them from most key engineering applications. Recent advances show that this long-standing strength-ductility dilemma can be controlled to a large extent by adopting novel design concepts based on powder metallurgy (PM). These include: 1) reinforcing the Ti matrix with a three-dimensional (3D) network-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 131 publications
0
4
0
1
Order By: Relevance
“…The reinforcement mechanism of TiB whiskers and TiC particles largely depends on their aspect ratio. Luo et al [ 47 ] point out that the increment of Ti6Al4V/TiB is linear with the aspect ratio of TiB whiskers. According to the SEM results (Figure 4), the aspect ratio of TiB w is less than 10.…”
Section: Resultsmentioning
confidence: 99%
“…The reinforcement mechanism of TiB whiskers and TiC particles largely depends on their aspect ratio. Luo et al [ 47 ] point out that the increment of Ti6Al4V/TiB is linear with the aspect ratio of TiB whiskers. According to the SEM results (Figure 4), the aspect ratio of TiB w is less than 10.…”
Section: Resultsmentioning
confidence: 99%
“…[ 16,17 ] It has been reported that the existence of TiB intensifiers and the new microstructure formed inside TiB‐TMC make TiB‐TMCs show excellent wear performance. [ 18,19 ] TiB is reinforced in TMCs by whiskers. According to the load sharing theory of whisker‐reinforced metal matrix composites, the load‐shearing effect of TiB is the main reason for the excellent wear resistance of coatings.…”
Section: Figurementioning
confidence: 99%
“…(TiBw+(TiZr) 5 Si 3 )/TA15钛基复合材料粉末冶金制备与热处理改性. 中国科学: 技术科学, 2020, 50: 935-946 要集中在熔铸法与粉末冶金法 [11,12] , 粉末冶金法制备 的复合材料中增强相的含量和分布易于精确控制、力 学性能高、同时复合材料构件易于一次性近净成 型 [3,10] . 近些年来, 3D打印增材制造技术、SPS快速烧…”
Section: 近年来 制备非连续增强钛基复合材料的方法主unclassified